Novel Insight Into Nutritional Regulation in Enhancement of Immune Status and Mediation of Inflammation Dynamics Integrated Study In Vivo and In Vitro of Teleost Grass Carp (Ctenopharyngodon idella): Administration of Threonine - Dong, Yu-Wen; Jiang, Wei-Dan; Wu, Pei; Liu, Yang; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhou, Xiao-Qiu; Feng, Lin (Frontiers in Immunology, 2022)
This study aims to investigate the effects of threonine (Thr) on immunoregulation in vivo and vitro of teleost grass carp (Ctenopharyngodon idella). Juveniles (9.53 ± 0.02 g) were reared for eight weeks with respective Thr diet (3.99, 7.70, 10.72, 14.10, 17.96 and 21.66 g/kg), then challenged with A. hydrophila for in vivo study. In vitro, Macrophages isolated from head kidney were treated for 48 h with L-Thr (0, 0.5, 1.0, 2.0, 4.0 and 8.0 mM) after 6h LPS induction. Results showed that, compared with Thr deficiency (3.99 g/kg), the optimal dietary Thr (14.10g/kg) affected the immunocytes activation in the head kidney (HK) and spleen (SP) by downregulating mRNA expressions of MHC-II and upregulating CD4 (not CD8), and mediated the innate immune by enhancing activities of Lysozyme (LZ) and acid phosphatase (ACP), content of complement 3 (C3) and C4, increasing mRNA abundances of Hepcidin, liver expressed antimicrobial peptide-2A (LEAP-2A), LEAP-2B and β-defensin1, downregulating tumor necrosis factor α (TNF-α), IL-6, IL-1β, IL-12p35, IL-12p40, IL-17AF1 and IL-17D partly by attenuating RORγ1 transcriptional factor, nuclear factor kappa B p65 (NF-κBp65) signaling cascades [IKKβ/IκBα/NF-κBp65] and upregulating transforming growth factor β1 (TGF-β1), IL-4/13A, -4/13B, IL-10 and IL-22 partly by GATA-3. Besides, the optimal dietary Thr regulated adaptive immune by upregulating mRNAs of immunoglobulin M(IgM) and IgZ (not IgD). In vitro, 2mM Thr downregulated mRNA abundances of colony stimulating factor-1 (CSF-1), inducible nitric oxide synthase (iNOS), mannose receptor 1 (MRC-1), matrix metalloproteinase2 (MMP-2) and MMP-9 significantly (P < 0.05), indicating that Thr could attenuate the M1 type macrophages’ activation. Moreover, L-Thr downregulated the mRNA transcripts of TNF-α, IL-6, and IL-1β associated with impairing SOCS1/STAT1 signaling and upregulate the IL-10 and TGF-β1 partly by accentuating SOCS3/STAT3 pathway. Above observations suggested that Thr improved immune status in immune organs of fish by enhancing the immune defense and mediating the inflammation process. Finally, based on the immune indices LZ activity in HK and C3 content in SP, the optimal Thr for immune enhancement in juvenile grass carp (9.53-53.43 g) are determined to be 15.70 g/kg diet (4.85 g/100 g protein) and 14.49 g/kg diet (4.47 g/100 g protein ), respectively.